A Generalized Approach for Computation of Near Field Radiation Pattern of an Antenna - Preetham Shankpal; Varun Arur; Govind Kadambi; James Shuttleworth (International Journal of Antennas and Propagation)
A generalized procedure in the form of an analytical formulation for the determination of radiation pattern of an antenna at any arbitrary distance which covers the near field as well as far field is presented in this paper. With the prior knowledge of either the current or field distribution on the radiating aperture, the proposed near field analysis is generic and can be applied for wide variety of antenna elements. The underlying principle of the generalized procedure is tantamount to considering the radiating aperture as an array of point electric and magnetic dipoles. The validity and novelty of the proposed new approach have been substantiated considering an open ended circular cylindrical waveguide and a conical horn as case studies and treating the far field as a special case of near field with pertinent distance criterion. The effect of change in the distance of observation ranging from reactive near field to far field on the radiation patterns of these antennas has also been discussed. The simulation studies reveal that the depicted normalized phase patterns of both the circular waveguide and conical horn follow the changes in the profile of the corresponding amplitude patterns.